Strategies in the Treatment of Distal Cerebellar Aneurysms: Report of a Series of 11 Patients - Harati, Ali; Mpotsaris, Anastasios; Lohmann, Frauke; Loehr, Christian; Weber, Werner; Puchner, Maximilian J. A. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Background Distal cerebellar artery aneurysms are rare entities and treatment modalities technically challenging. In recent years, new therapeutic options have emerged through microsurgical and endovascular means.Objective Based on a series of 11 cases, we describe combined interdisciplinary treatment strategies and report the outcome in a midterm follow-up interval of 12 months.Methods Collection of clinical case data during acute phase and follow-up including standardized angiographic control intervals during follow-up and assessment of the outcome.Results 7 of 11 reported cases had flow-related aneurysms based on an underlying arteriovenous malformation (AVM) or dural arteriovenous fistula (DAVF); we found multiple aneurysms in four cases. All patients with flow-related aneurysms presented with subarachnoid hemorrhage (SAH). Only one of four patients in this series without an underlying AVM or DAVF presented with SAH that was attributable to a distal cerebellar aneurysm. In one case, we observed a de novo formation of two flow-associated distal aneurysms (10 years interval). Two patients were treated conservatively, five patients were treated endovascularly, one patient was treated surgically and three patients were treated with combined methods. 9 of 11 patients with initial SAH had a good outcome.Conclusions Distal cerebellar aneurysms associated with AVM or DAVF are rare but characterized by a high risk of hemorrhage. The present series indicates that an experienced interdisciplinary team and the combination of available techniques may lead to a reduction of complications and to a better outcome.
Keywords: intracranial aneurysm; arteriovenous malformation; posterior fossa; SAH